Increase in soluble PD-1 is associated with prolonged survival in patients with advanced EGFR-mutated non-small cell lung cancer treated with erlotinib. (October 2016) - Sorensen, Steffen Filskov; Demuth, Christina; Weber, Britta; Sorensen, Boe Sandahl; Meldgaard, Peter
Highlights: Serum concentration of sPD-1 increase during erlotinib treatment. Increase in serum concentration of sPD-1 during erlotinib treatment is associated with improved survival. Dynamics of sPD-1 are not associated with clinic-pathological parameters. Dynamics of sPD-1 are not associated with the emergence of T790M in ctDNA. Abstract: Objectives: The central immune co-inhibitory programmed cell death receptor/ligand 1 (PD-1/PD-L1) pathway plays a key role in tumor immune evasion in non-small cell lung cancer (NSCLC). Soluble PD-1 (sPD-1) can be detected in the blood, and preclinical evidence suggests that sPD-1 blocks PD-1/-L1 interaction and improves anti-tumor immunity. The present study compares the concentration of sPD-1 in the serum of advanced NSCLC patients with Epidermal Growth Factor Receptor ( EGFR ) mutation prior to erlotinib treatment and at the time of progression and correlates these results to patient outcome. Materials and methods: Blood samples from 38 patients with EGFR -mutated advanced NSCLC treated with erlotinib were analyzed for sPD-1 by sandwich ELISA. EGFR mutational status was assessed in circulating tumor DNA (ctDNA) and tumor biopsies. Results: sPD-1 could be detected in 21% of patients prior to erlotinib treatment, and at disease progression in 37% (p = 0.015). An increase in sPD-1 during erlotinib therapy was found in 34%, a decrease in 8% and no change in 58% of patients. An increase in sPD-1 during treatment was associated with prolonged progression-free (adjusted HR 0.32, p = 0.013) and overall survival (adjusted HR 0.33, p = 0.006), but not associated with the emergence of EGFR T790M mutation in ctDNA at progression or any clinicopathological factors. Conclusion: Patients with an increase in sPD-1 during erlotinib treatment have a more favorable outcome. Our results emphasize the vast clinical impact of the PD-1/PD-L1 axis, and support the existing preclinical evidence in the bioactive function of sPD-1.